Avaliação imunoistoquímica do EGFR / Her -1 em leucoplasias bucais - Daniela Cotta Ribeiro (2009)
Leukoplakia is the most common precancerous lesion of the oral cavity.The presence of epithelial dysplasia and clinical characteristics such as tobacco consumption and location are important predicting factors of malignant transformation. Epidermal Growth Factor Receptor (EGFR) is a member of a family of tyrosine-kinase receptor that plays an important role in the control of cell growth. A high expression of EGFR is frequently observed in many solid tumors including Oral Squamous Cell Carcinoma (OSCC). The aim of the present study was to evaluate the immunoexpression of EGFR on 48 oral leukoplakias searching the association of EGFR with tobacco consumption, location (high/low risk), grade of epithelial dysplasia, and cell proliferation through immunohistochemistry for Ki-67 and p27. EGFR was positive in 62,5%of leukoplakias. EGFR immunoexpression showed a significant difference between leukoplakias of high and low risk sites. p27 immunoexpression was also significantly different between positive and negative EGFR leukoplakias. The p27 index lowered with the severity of dysplasia. We did not find an association of EGFR with tobacco and Ki-67 immunoexpression. The results show that EGFR is expressed in leukoplakias independently of dysplasia. The association of EGFR and p27 merits further investigation.